Maisie and the dolphin - Rabley, Stephen (Essex : Penguin, 2001)
Maisie lives in Caribbean. She is unhappy because her parents haven't got enough money to keep their animal hospital open.
Keywords: Animals-childrens friendship. -- Fiction; Dolphines -- Fiction